Traumatic brain injury series - Introduction - Ingrid Hoeritzauer; Colette Griffin (Advances in Clinical Neuroscience & Rehabilitation)
The early rehabilitation of patients with traumatic brain injury (TBI) has been demonstrated to be both clinically and economically effective [1,2]. Neurologists, neurosurgeons and neurorehabilitation specialists all have a role to play in the assessment and management of this patient group.